MANAJEMEN KARIR DAN PENGEMBANGAN KARIR PADA ORGANISASI TANPA BATAS - Ratna Kusumawati (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
Business environment and organizational changing is implied on boundary less organization rising, that is paradigm changing which states if organization is fewer on bondary between person, information and talent of human resources. On career in boundary less organization era, they must do new career management model. The new model is restructure from the traditional. The employee roles as career strategist not as career planner and enterprise roles on organizational management so it could improve work productivity of employee and next it will turn improve of efficiency of organization working.Key words : Boundary less organization, career management, career development.